Optimalisasi produksi antimikrobia oleh Lactobacillus sp. TGR-2=Optimization of Antimicrobial Substance Production by - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
AcH, by Pediococcus acidilactici H. App . . Food and Nutrition Development and Reseach Center. Gadjah Mada University, Yogyakarta. in press. . Antimicrobial substance from lactic acid bacteria, especially those involved in fermented food are preferable to be used as food preservatives due to their safety. In this study, production of an antimicrobial substance by Lactobacillus sp. TGR-2 isolated from growol, has been carried out. The antimicrobial activity was determined by turbidimetric assay using Staphylococcus aureus FNCC 0047 as microbial indicator. The result showed (erlenmeyer scale) that the maximum production of the antimicrobial substance was obtained when MRS broth used as fermentation medium with it's initial pH 6.0, incubation at 30Â°C for 16-24 hours with the antimicrobial activity 1.93 UA /mL. Addition of glucose to MRS broth at final concentration 0.5%, yeast extract 1.6%, glucose 0.5% and 1.6% yeast extract, Na S03 0.025% or salt buffer containing 0.6% dip otassium phosphate, sodium ecetate 1.5% and 0.6% triammonium citrate increased the production of the antimicrobial substance up to 18, 46, 60, 17 and 46%. In contrast, addition of biotin and B-complex vitamin of 0.5 mg/mL, 1% NaCl, 0.6 g/1 Me', 0.15 g/L Mn' did not increase the production. Anaerobic/aerobic conditions during fermentation have no influence to the antimicrobial substance production, whereas, maintained the pH at a constant level (pH 5.0) increased the production up to 3.56 UA/mL. Fermentor scale (batch) with medium volume 1.5 L, maximum production was accomplished by utilizing MRS broth medium containing 0.5% glucose, 1.6% yeast extract, 0.6% dipotassium phosphate, 1.5% sodium acetate and 0.6% trianunonium citrate, with the following condition: initial pH of 6.0, incubation temperature of 30Â°C and duration of 16-24 hours, with the antimicrobial activity 5.27-5.77 UA/mL.